Lack of Catch-Up Growth with Growth Hormone Treatment in a Child Born Small for Gestational Age Leading to a Diagnosis of Noonan Syndrome with a Pathogenic PTPN11 Variant - Daniel J. Olivieri; Lauren J. Massingham; Jennifer L. Schwab; Jose Bernardo Quintos (Case Reports in Endocrinology)
Background. Growth hormone (GH) treatment increases the adult height of short children born small for gestational age (SGA). Catch-up growth is associated with a younger age, shorter height, and prepubertal status at the onset of GH treatment. We report a 12 11/12-year-old girl born SGA who received GH for 5 years without catch-up growth and was diagnosed with Noonan Syndrome (NS). Results. A 5-year-and-9-month-old 46, XX girl born SGA was started on GH treatment at a dose of 0.32 mg/kg/week. Her midparental target height is 158.6 cm. Endocrine work up showed an IGF-1 level 69 ng/ml (Normal (N): 55–238 ng/ml), IGFBP3 2.6 mg/L (N: 1.9–5.2 mg/L), TSH 3.2 mIU/L (N: 0.35–5.5 mIU/L), and a normal skeletal survey. Height was 96 cm (0.1%; Ht SDS −2.9), weight 14 kgs (1%; Wt SDS −2.3), and Tanner 1 breast and pubic hair were observed. Due to the poor catch-up growth on GH treatment, she was referred to Genetics to elucidate genetic or syndromic causes of short stature. She was noted to have posteriorly rotated ears and slight down slanting of the palpebral fissures. Genetic findings showed a heterozygous pathogenic variant in PTPN11 (c.922A > G (p.Asn308Asp)) diagnostic for NS. This finding is de novo given negative parental testing. She was noted to have a heterozygous missense variant of unknown significance (VUS) in FGFR3: c.746C > A (p.Ser249Tyr). FGFR3 is associated with multiple skeletal dysplasias including thanatophoric dysplasia, achondroplasia, and Crouzon syndrome and hypochondroplasia. Clinical correlation is poor for these syndromes. Conclusion. Diminished catch-up growth and response to GH treatment in a child born SGA led to the diagnosis of NS. The concomitant diagnosis of SGA and NS may have affected the responsiveness of this child to the growth promoting effect of GH treatment.